Optimization of the Real-Time Quaking-Induced Conversion Assay for Prion Disease Diagnosis - Zerr, Inga; Cramm, Maria; da Silva Correia, Susana Margarida; Zafar, Saima; Villar-Piqué, Anna; Llorens, Franc; Schmitz, Matthias (Frontiers in Bioengineering and Biotechnology, 2020)
The real-time quaking-induced conversion (RT-QuIC) assay is a highly reproducible and robust methodology exhibiting an excellent pre-mortem diagnostic accuracy for prion diseases. However, the protocols might be time consuming and improvement of the detection technology is needed. In the present study, we investigated the influence of a pre-analytical cerebrospinal fluid (CSF) treatment with proteinase K (PK) on the kinetic of the RT-QuIC signal response. For this purpose, we added PK at different concentrations in RT-QuIC reactions seeded with Creutzfeldt-Jakob-disease (sCJD) CSF. We observed that mild pre-analytical PK-treatment of CSF samples resulted in an increased seeding efficiency of the RT-QuIC reaction. Quantitative seeding parameters, such as a higher area under the curve (AUC) value or a shorter lag-phase indicated higher conversion efficiency after treatment. The diagnostic accuracy resulting from 2 µg/mL PK treatment was analysed in a retrospective study, where we obtained a sensitivity of 89%. Additionally, we analysed the agreement with the previously established standard RT-QuIC protocol without PK treatment in a prospective study. Here, we found an overall agreement of 94% to 96% between both protocols A Cohens kappa of 0.9036 (95% CI: 0.8114 - 0.9958) indicates an almost perfect agreement between both protocols. In conclusion, the outcome of our study can be used for a further optimization of the RT-QuIC assay in particular for a reduction of the testing time.